Exploiting social influence in networks - Vladyslav Nora; Eyal Winter (Theoretical Economics, 2024)
We study binary action network games with strategic complementarities. An agent acts if the aggregate social influence of her friends exceeds a transfer levied on the agent by a principal. The principal seeks to maximize her revenue while inducing everyone to act in a unique equilibrium. We characterize optimal transfers showing that agents who are more popular than their friends receive preferential treatment. Our main result is that under mild conditions complete core–periphery networks deliver the highest revenue to the principal. Furthermore, we show that the revenue is higher in networks where links are allocated unequally across agents. Hence, the principal benefits from creating “influentials” by linking well-connected hubs to less popular periphery.
Keywords: C72; D82; 330; Social networks; split graphs; strategic complementarities; unique implementation